Translating William Wordsworth's Poetry into Indonesian: Strategies Employed by English Literature Students - Halimi, Sisilia Setiawati; Fardiansyah, Muhammad Farrel (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Poetry is a literary art that can be difficult to translate, considering its interpretations and the gap between languages. Previous related studies have yet to provide a deeper investigation into problems of poems and translation from students’ points of view. Filling in the gap, this study uses a qualitative method to examine the dominantly utilized translation method, the difficulties encountered, and how such difficulties were tackled. Twelve English Literature students were involved in translating a poem and answering interview questions. The data were analyzed using the poetry translation methods by André Lefevere (1975) and complemented by a written interview to further discuss the students’ perspectives. The results revealed that literal translation is the dominant method used. Problems related to diction in the target text were their main difficulty. Analyzed from their interview responses, the strategies utilized include consulting dictionaries, using descriptive equivalents, finding alternative terms online, and so on. This study concludes that the translation difficulties encountered leaned more toward language production skills and that poem translators should have a strong familiarity with both languages and an interest or expertise in poems. Translation studies should provide more exposure to Indonesian poems to increase familiarity with Indonesian literary diction.